Development of Instant Microbial Starter for Production of Fermented Cassava Flour: Effect of Vacuum Drying Temperature, Carrier Media, and Storage Temperature - Kresnowati, Made Tri Ari Penia; Bindar, Yazid; Rahmina, Fathya (Journal of Engineering and Technological Sciences, 2018)
Cassava is an important crop for tropical countries such as Nigeria, Brazil, Thailand, and Indonesia. The potential utilization of cassava in the food industry can be enhanced by processing cassava into fermented cassava flour (fercaf), which has been shown to have a neutral color and aroma as well as low cyanogenic content. The use of specific microbial starter in the cassava chip fermentation for fercaf production will direct the fermentation process, maintaining a high quality of the produced flour. Thereby, the availability of an easy-to-use microbial starter is important for the production of fermented cassava flour. The aim of this study was to evaluate vacuum drying methods in the preparation of microbial starter for fermented cassava flour production. In particular, the effects of carrier media, drying and storage temperature on cell viability in dry starter were tested. The results showed that different methods should be applied to different microbial species. Bacillus subtilis and Aspergillus Oryza should be prepared using fercaf as the carrier media at a drying temperature of 55 °C, whereas Lactobacillus plantarum starter should be prepared using skim milk as the carrier media at a drying temperatur of 40°C. Apart from B. subtilis, the starters should be stored in a refrigerator.